THE ISSUE OF GENRE CRITERIA IN DEFINING QUATRAIN POEMS - Jurayeva Sojida Ravshankulovna (Bright Mind Publishing, 2026)
The article deals with the study of classical and modern manifestations of poetic genres in the form of a torlik in Uzbek literary criticism of the 20th century. In particular, the issue of genre criteria in distinguishing quatrain-shaped murabba's from each other, tradition and innovation, confusion and mutual differences are highlighted based on the scientific analysis of research.
Keywords: Genre criterion, aruz, barm, tradition and innovation, “qit'aiy” (qit'a), “taronaiy” (tarona rubaiy), “rubaiyona” (ordinary rubaiy) and “murabba'-she'r” (murabba').